Relaxor regulation and improvement of breakdown strength for Bi0.5Na0.5TiO3-based ceramics by co-doping with Ca and Nb. Issue 7 (1st April 2022) - Jiang, Zehua; Yuan, Ying; Yang, Hongcheng; Li, Enzhu; Zhang, Shuren
Abstract: In this paper, the dense perovskite structure ceramics (Na0.3 Bi0.3 Ba0.04 Sr0.36 )1-x Cax Ti1-x Nbx O3 were investigated. The long-range order structure was destructed by structural distortion, and the relaxor behavior was enhanced after the co-doping with Ca and Nb. Meanwhile, the restraint of oxygen vacancy resulted in low leakage current density and small grain size with the increase of breakdown strength ranging from 210 to 280 kV/cm. The high recoverable energy density ( W rec = 2.94 J/cm 3 ) with high efficiency ( η = 91.04%) was obtained at x = 0.03, along with fast discharge speed ( t 0.9 –180 ns), high power density ( P D = 56.15 MW/cm 3 ), superior cycle stability and thermal stability. The properties guaranteed a promising and practical prospect in pulsed power systems.